2020
DOI: 10.3390/ani10061021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feeding Improved Grass Hays and Eragrostis tef Straw Silage on Milk Yield, Nitrogen Utilization, and Methane Emission of Lactating Fogera Dairy Cows in Ethiopia

Abstract: The nutritionally imbalanced poor-quality diet feeding is the major constraint of dairy production in tropical regions. Hence, alternative high-quality roughage-based diets are required to improve milk yield and reduce methane emission (CH4). Thus, we tested the effects of feeding natural pasture hay, improved forage grass hays (Napier and Brachiaria Hybrid), and treated crop residues (Eragrostis tef straw) on nutrient digestibility, milk yield, nitrogen balance, and methane emission. The eight lactating Foger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…Together with the significantly lower DM digestibility in CG1 than in GG, these findings suggest that natural-grassland hay is not a suitable feed for indoor feeding. The lower CH 4 emissions per DM intake in CG2 than in CG1 were consistent with the findings of a previous report [ 17 ], and with those of another report that demonstrated that a less fibrous diet with a low NDFom concentration ( i.e ., CG2) decreases CH 4 emissions [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Together with the significantly lower DM digestibility in CG1 than in GG, these findings suggest that natural-grassland hay is not a suitable feed for indoor feeding. The lower CH 4 emissions per DM intake in CG2 than in CG1 were consistent with the findings of a previous report [ 17 ], and with those of another report that demonstrated that a less fibrous diet with a low NDFom concentration ( i.e ., CG2) decreases CH 4 emissions [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…The concentrations of the crude protein and NDFom (72.1%) in the natural-grassland hay were consistent with those in the previous study (crude protein, 4.2%; NDFom, 74.2% [17]). These findings appeared to suggest that natural-grassland hay could not be used as a basal diet for the Fogera dairy cows, and that a concentrate supplement would be needed if naturalgrassland hay were fed as the basal forage.…”
Section: Effects Of Grazing Versus Indoor Feeding On Productivity and Ch 4 Emissions Of Dairy Cowssupporting
confidence: 91%
See 3 more Smart Citations